Balance disorders and vertigo as a complications of COVID-19 - Piotrowski, Jan; Nowińska, Bianka (Family Medicine & Primary Care Review, 2023)
COVID-19 is a disease caused by a new type of SARS virus. COVID-19 clinical symptoms are primarily related to the respiratory system but may also be involved in many others, including the nervous system. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can be an aetiological factor responsible for balance disorders. Symptoms such as vertigo may coexist with other symptoms or be an isolated manifestation of the disease. Among other balance dysfunctions associated with COVID-19 are BBPV (benign paroxysmal positional vertigo), vestibular neuritis, acute labyrinthitis, acute cerebellitis, as well as Ménière’s disease. MRI, Videonystagmographic (VNG) and the Dix-Hallpike test are used to make a diagnosis. Improvements were observed after treatment with oral corticosteroids and vestibular physiotherapy along with intratympanic injection of dexamethasone. Antiemetics, antihistamines, anti-cholinergics and benzodiazepines drugs may be helpful in relieving symptoms. In addition, drugs used in scheduled treatment of COVID-19, such as azithromycin and hydroxychloroquine, may cause balance disorders due to their potential side effects. The following article presents cases of COVID-positive patients with balance disorders. The aim of this article was to raise awareness that nonspecific symptoms such as balance disorders may be the only manifesta-tion of COVID-19, which is important due to early diagnosis and administration of treatment.